Physical Stability of Binahong Leaf Extract (Anredera cordifolia (Ten.) Steenis) with Hydroxypropyl Methylcellulose and Hydroxyethyl Cellulose Gelling Agents - Siska Purnama Sari; Abdul Karim Zulkarnain (Majalah Obat Tradisional, 2023)
Second-degree burns have the highest prevalence and often occur in the household environment. The healing process can be accelerated by traditional medicine. One of the many plants known to have wound-healing abilities is the Binahong plant (Anredera cordifolia (Ten.) Steenis). The gel preparation is chosen because of the many benefits it can provide. The gelling agents used were Hydroxypropyl Methyl Cellulose and Hydroxyethyl Cellulose. The combination of these gelling agents was chosen because both agents are capable of producing gel preparations with good stability during storage. Therefore, the optimization was carried out to obtain the optimum formula that met the requirements. The observed responses were organoleptic, pH, spreadability, adhesion, viscosity, and homogeneity. The data obtained was optimized with the Simplex Lattice Design program in Design Expert software version 13.0.0. The results of the verification test were compared for their significance with the T-test with a 95% confidence level. The optimum gel stability of Binahong leaves (Anredera cordifolia (Ten.) Steenis) was tested using one-way ANOVA and post hoc. The results showed that the optimum formula for Binahong leaf extract gel (Anredera cordifolia (Ten.) Steenis) was obtained with a composition ratio of 0.5% HPMC and 4.5% HEC. The verification results obtained valid values for pH response, viscosity, and spreadability according to SLD predictions. The optimum formula for Binahong leaf extract gel (Anredera cordifolia (Ten.) Steenis) was stable during the cycling test.